2019
DOI: 10.1159/000501555
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Imaging Features and Postnatal Factors Associated with Gastrointestinal Morbidity in Congenital Diaphragmatic Hernia

Abstract: <b><i>Background:</i></b> To perform a comprehensive assessment of postnatal gastrointestinal (GI) morbidity and determine the prenatal imaging features and postnatal factors associated with its development in patients with congenital diaphragmatic hernia (CDH). <b><i>Materials and Methods:</i></b> A retrospective review was conducted of all infants evaluated for CDH at a quaternary fetal center from February 2004 to May 2017. Prenatal imaging features and postna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…the incidence of GERD (defined by upper gastrointestinal tract endoscopy and esophageal pH‐metry) at 1 year of age was 46% in 26 CDH survivors, half of whom had no significant symptoms. Verla et al 26 . found an association of a large defect, patch repair and use of ECMO with GERD, gastrostomy tube placement and fundoplication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the incidence of GERD (defined by upper gastrointestinal tract endoscopy and esophageal pH‐metry) at 1 year of age was 46% in 26 CDH survivors, half of whom had no significant symptoms. Verla et al 26 . found an association of a large defect, patch repair and use of ECMO with GERD, gastrostomy tube placement and fundoplication.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Koivusalo et al 8 , the incidence of GERD (defined by upper gastrointestinal tract endoscopy and esophageal pH-metry) at 1 year of age was 46% in 26 CDH survivors, half of whom had no significant symptoms. Verla et al 26 found an association of a large defect, patch repair and use of ECMO with GERD, gastrostomy tube placement and fundoplication. They also found an association between stomach displacement on prenatal imaging and GIM at 6 months of age in cases of left-sided CDH.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Verla et al, pointed several possible factors for GER; slow pulmonary expansion of the affected side, size of defect, malposition of the stomach, use of mechanical ventilation, or extracorporeal membrane oxygenator. [6] Marseglia et al, proposed increased intra-abdominal pressure after closure of the abdominal defect, motility disturbance of the upper gastrointestinal tract, or damage of esophageal peristaltic pump, as possible causes of GERD in cases of CDH. [7] There was a correlation between GER and early detection of CDH in prenatal studies and the presence of polyhydramnios.…”
Section: Discussionmentioning
confidence: 99%
“…Verla observed that larger defects and intrathoracic stomach displacement on prenatal MRI were significantly associated with the diagnosis of GERD, but an intrathoracic liver was not. On the other hand, these variables were not associated with the need of anti-reflux surgery ( 55 ). Cordier et al found that stomach position on prenatal ultrasound was independently associated with GER.…”
Section: Gastroesophageal Refluxmentioning
confidence: 99%
“…Several post-natal factors are associated with an increased risk of GER, including right-sided CDH, management with non-conventional mechanical ventilation such as high frequency oscillatory ventilation, need for nitric oxide (NO) and ECMO, the need for patch closure and liver within the chest ( 55 , 58 ). On multiple variable analysis, however, Diamond et colleagues demonstrated that only liver in the chest and patch repair were significant predictors of GER.…”
Section: Gastroesophageal Refluxmentioning
confidence: 99%